Structural evolution of Pico del Águila anticline (External Sierras, southern Pyrenees) derived from sandbox, numerical and 3D structural modelling techniques - O. VIDAL-ROYO; J.A. MUÑOZ; S. HARDY; H. KOYI; N. CARDOZO (Geologica Acta, 2013)
This paper reports on the integration of different modelling techniques to construct a unified conceptual model of structural evolution of the Pico del Águila anticline (External Sierras, southern Pyrenees, Spain). The structure is a well-known example of a detachment fold, which exhibits a N-S structural trend, perpendicular to the general structural trend of the southern Pyrenees (mainly E-W). Based on field observations of an unevenly distributed Triassic décollement, analogue modelling shows how to generate orogen-perpendicular structures which may result in transverse anticlines. The models show how contrasts between high and low friction patches in the basal décollement led to the formation of structures at high angle, centered over the high friction areas. Numerical models investigate the effect of a complex mechanical stratigraphy, characterized by an interlayering of competent and incompetent layers, plus syn-kinematic sedimentation in the fold growth. Based on field data and seismic interpretations, a 3D reconstruction and sequential geomechanical restoration of the Pico del Águila anticline suggests the coexistence of multiple folding mechanisms occurring simultaneously in different units and structural domains of the fold, leading to a complex strain pattern that can not be assessed by simplistic kinematic 2D approaches. By integrating the models with previous data in the region, the benefits and drawbacks of each modelling technique are discussed and an integrated model of structural evolution for the Pico del Águila anticline is presented. This enables a better comprehension of the structure as well as of the processes that drove the evolution of the N-S detachment anticlines in the External Sierras of the southern Pyrenees.